Prevalence of Hypertension and its Associated Factors among Retired Army in Pokhara - Ranjitkar, Shreena; Sharma, Sunita (Janapriya Journal of Interdisciplinary Studies, 2021)
Hypertension can be caused by a number of factors. Tobacco usage, excessive alcohol use, a poor diet, high salt intake, verweight and obesity, and physical inactivity are among these factors. Demographic factors such as age, ethnicity and family history also play a role in causing hypertension. When inherited factors are paired with an unhealthy lifestyle, the chance of high blood pressure rises. A cross-sectional descriptive research design was used for this study. Non probability purposive sampling was done to select the sample. Three hundred and fifteen retired army were chosen as a sample. Semi- structured interview schedule was used to collect data. Over all prevalence of hypertension was 58.41% with newly diagnosed cases of 33(10.4%) and previous cases of 151(47.9%) and this was significantly associated with Age, years of retirement, smoking, chewing tobacco and salt consumption. The burden of hypertension was high, and it has become a major health concern among retired army. To deal with life-threatening consequences and chronic debilitating morbidity, a community screening program, timely detection, lifestyle adjustment, treatment, and prevention are all critical.